Histopathological Subtypes of Basal Cell Carcinoma and Associated Pathological Features: A Prospective Study from Western Nepal - Gautam Ghimire, Pragya; Ghimire, Prasanna; Sharma Paudel, Ramesh; Aryal, Alisha; Jaiswal, Ruhi (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Background: Basal cell carcinoma (BCC) is the most common skin malignancy globally. Histopathological subtype influences prognosis and treatment selection, yet prospective data from Nepal remain limited. Objectives: To determine BCC subtype distribution, describe associations between morphology and pathological parameters, and identify high-risk features relevant to treatment planning at a Western Nepal referral center. Materials and Methods: We prospectively studied 35 consecutive histopathologically confirmed BCC cases at a tertiary care hospital in Western Nepal from September 1st, 2023, to August 31st 2025. Two observers independently reviewed hematoxylin and eosin-stained slides, evaluating subtype distribution, demographics, anatomical site, tumor depth, surgical margin status, perineural invasion, and ulceration. Results: Nodular BCC predominated (68.6%, n=24), with pigmented nodular variant most frequent (45.7% of all cases, n=16). Male to female ratio was 1.7 to 1; mean age 64.3±9.2 years. All cases were from head and neck sites, cheek/periocular region most common (57.1%, n=20), followed by nose/ear (31.4%, n=11). High-risk subtypes (n=7, 20%) showed higher biopsy margin involvement (71.4% vs 14.3%), greater mean invasion depth (2.8±1.1 mm vs 1.4±0.6 mm), and increased ulceration (57.1% vs 17.9%) compared to low-risk subtypes. Conclusion: Pigmented nodular BCC is the predominant subtype in Western Nepal. High-risk histopathological patterns suggested increased adverse features, including higher biopsy margin involvement. These findings are consistent with previously reported associations between high-risk histological patterns and adverse pathological features; however, validation with clinical outcome data is required.